DESCRIPTION OF POSTPARTUM EXERCISE FOR UTERINE INVOLUION IN Mrs. A WITH SPONTANEOUS POSTPARTUM IN SELAKAMBANG - Umu Nurul Azizah; Priyatin Sulistyowati; Wiwik Priyatin (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Uterine involution is the process by which the uterus returns to its pre-pregnancy condition and weighs around 60 grams. This process begins immediately after the placenta is delivered due to contraction of the smooth muscles of the uterus, measurement of uterine involution and also by expulsion of the lochea. One way to treat uterine involution is through postpartum exercise to accelerate the decrease in the height of the uterine fundus. Objective: To determine the description of postpartum exercise on the speed of uterine involution in postpartum mothers. Method: This research is a type of qualitative research designed as a case study method. Results: After doing postpartum exercise for 7 days with a duration of 10- 15 minutes, the height of the uterine fundus can be reduced by 9 cm from 12 cm on the first day to 3 cm on the 7th day. Conclusion: postpartum exercise can influence the uterine involution process in postpartum mothers, and the speed of uterine involution in postpartum mothers who do exercise is fast